Butterflies and Ribbons: Supporting Families Experiencing Perinatal Loss in Multiple Gestation - Béatrice Boutillier; Nicholas D. Embleton; Sophie Bélanger; Alexie Bigras-Mercier; Audrey Larone Juneau; Keith J. Barrington; Annie Janvier (MDPI AG, 2023)
Introduction: In neonatology, multiple pregnancies are common. Unfortunately, it is not rare for one baby to die. Communication with parents in these circumstances has been demonstrated to be sub-optimal. Methods: Two educational programs were evaluated with pre- and post-course surveys, questionnaires administered to participants, and audits. Results: In the online Butterfly project (UK; n = 734 participants), all participants reported that the training exceeded or met their expectations, 97% reported they learned new skills, and 48% had already applied them. Participants expressed gratitude in their open-ended answers: "I feel a lot more confident in supporting parents in this situation". In the Ribbon project (workshop for neonatal clinicians, Quebec; n = 242), 97% were satisfied with the training and reported feeling more comfortable caring for bereaved parents. Knowledge improved pre-post training. Audits revealed that 100% of cases were identified on the incubator and the baby's/babies' admission card, all changed rooms after the death of their co-twin/triplet, and all had the name of their co-twin/triplet on the discharge summary. All clinicians (55) knew what the ribbon symbol meant when asked during surprise audits at the bedside. Conclusion: Different educational strategies to optimize communication with families after the perinatal loss of a co-twin are appreciated and have a positive impact.